Detection of Ge and Si intermixing in Ge/Si using multiwavelength micro-raman spectroscopy - Yoo, Woo Sik (2015)
To meet various physical property requirements of materials for advanced application, for specific devices, combinations of Si/Ge, Ge/Si, Si1-xGex/Si, are frequently introduced in the device fabrication process. Epitaxy, condensation and annealing processes are commonly used. Since a small variation in composition, strain and crystallinity can result in reduced device performance or failure, the composition, strain and crystallinity must be carefully monitored and controlled throughout the manufacturing process. We report the detection of Ge and Si intermixing in epitaxially grown Ge/Si after successive thermal anneals using multiwavelength Raman spectroscopy. We have studied the dependence of Ge and Si intermixing on annealing temperature and Raman excitation wavelength. Very strong dependence of signal-to-noise (S/N) ratio measurements on excitation wavelength and film structure was observed. Suitable excitation wavelengths must be chosen to properly detect and characterize Si and Ge intermixing, based on the stacking order of epitaxial films and thicknesses.